Impact of acute pancreatitis during pregnancy in Chinese women: a meta-analysis - Zhao Haiyan; Peng Na; Gao Yong; Bai Xiumei; Bai Jianying (Taylor & Francis Group, 2022)
AbstractA random-effects meta-analysis was performed in English and Chinese databases since its inception to August 2020 to assess the incidence, causes and severity of acute pancreatitis (AP) at various stages of pregnancy, maternal and foetal mortality. A total of 154 articles representing 4034 patients with AP during pregnancy in China were included for the analysis. The incidence of AP during pregnancy was 0.0469 (95% confidence interval [CI], 0.0349; 0.0627) in the first trimester, whereas it was 0.2518 (95% CI, 0.2210; 0.2854) and 0.6323 (95% CI, 0.5870; 0.6753) in the second and third trimester, respectively. The major causes of AP were hypertriglyceridaemia (0.351 [95% CI, 0.3202; 0.3834]) and biliary pancreatitis (0.424 [95% CI, 0.4094; 0.5002]). The severity of AP was mild in majority of the patients. The incidence of AP at maternal mortality was 0.0184 (95% CI, 0.0126; 0.0269) and foetal mortality was 0.1018 (95% CI, 0.0867; 0.1192). Our meta-analysis revealed that hypertriglyceridaemia and biliary pancreatitis remain the major causes of AP during pregnancy. Foetal mortality requires further investigation. IMPACT STATEMENTWhat is already known on this subject? Acute pancreatitis (AP) in pregnant women is characterised by acute onset and delay in understanding the interaction of the metabolic changes with pancreatic pathophysiology, and thus becomes difficult to diagnose the disease and provide timely treatment to the patients. This poses a greater health risk among women and their foetus by increasing their chances of mortality.What the results of this study add? We performed an exhaustive, random-effects meta-analysis involving 154 articles representing 4034 patients to assess the incidence of AP at various stages of pregnancy, the causes of AP and the severity of AP during pregnancy, maternal and foetal mortality.What are the implications of these findings for clinical practice and/or further research? Our meta-analysis revealed that hypertriglyceridaemia and biliary pancreatitis remain the major causes of AP during pregnancy. Although the rates of maternal mortality have decreased in the recent years, foetal mortality still remains high and requires further investigation.